Finding a place and a voice: marginality and women´s poetry in Colombia (2022)
This article reviews the poetry written by women in Colombia in the period between the second half of the nineteenth century and the first half of the twentieth century, focusing on the publication of their first books of poems took place. From this initial breaking into the literary field, we propose to evaluate how these women authors created a place for themselves in poetry. On the one hand, the social and pragmatic aspects of this phenomenon are reviewed according to the concepts of literary field and literary institution of Bourdieu and Dubois, respectively; and, on the other, through the analysis of what happened in the field of the poetic word. The results show that the effort of women to enter the literary field had two gestures to highlight: the claim of a place that required seeking legitimacy and the need to find their own voice, on the margins of the canonical, which made them advance towards a postmodernist poetry.